2010
DOI: 10.1007/s11894-009-0088-1
|View full text |Cite
|
Sign up to set email alerts
|

Viral Resistance in Hepatitis B: Prevalence and Management

Abstract: Hepatitis B is a DNA virus affecting hundreds of millions of individuals worldwide. As the clinical sequelae of cirrhosis and hepatocellular cancer are increasingly recognized to be related to viral levels, the impetus increases to offer treatment to those previously not treated. With the development of more robust antivirals with reasonable safety profiles, long-term treatment is becoming more common. The oral nucleos(t)ide analogs have become the preferred first-line therapies for most genotypes of hepatitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…In previous studies, it was observed that the LMV resistance mutations, rtV173L, rtL180M, and rtM204V, resulted in the reduced binding of antibodies to the neutralization domain (“a” determinant) of the HBsAg [Torresi et al, 2002; Sloan et al, 2008]. Also, the rtV173L mutation, which accompanies rtL180M and rtM204V in about 10–20% of cases during LVD use, allows improved HBV replication fitness [Delaney et al, 2003; Poordad and Chee, 2010]. Moreover, genotypic resistance to TDF has been detected in several patients with HIV‐HBV co‐infection, and the substitution rtA194T (plus rtL180M and rtM204V) has been associated with TDF resistance [Sheldon et al, 2005; Zoulim and Locarnini, 2009].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, it was observed that the LMV resistance mutations, rtV173L, rtL180M, and rtM204V, resulted in the reduced binding of antibodies to the neutralization domain (“a” determinant) of the HBsAg [Torresi et al, 2002; Sloan et al, 2008]. Also, the rtV173L mutation, which accompanies rtL180M and rtM204V in about 10–20% of cases during LVD use, allows improved HBV replication fitness [Delaney et al, 2003; Poordad and Chee, 2010]. Moreover, genotypic resistance to TDF has been detected in several patients with HIV‐HBV co‐infection, and the substitution rtA194T (plus rtL180M and rtM204V) has been associated with TDF resistance [Sheldon et al, 2005; Zoulim and Locarnini, 2009].…”
Section: Discussionmentioning
confidence: 99%
“…Foremost, it is imperative that children are carefully selected for therapy. The experience with lamivudine in children and the known resistance rates associated with long-term adefovir and telbivudine have tainted enthusiasm for embarking on prolonged therapies for children when the risk-benefit ratio has not been studied [38]. Because young children are rarely at imminent risk of advanced disease, waiting for the development of a better therapy, or waiting until spontaneous seroconversion occurs, can be an appropriate option.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, resistance developed after 135 weeks of adefovir treatment; viral rebound developed in the majority of patients with genotypic resistance [37]. There is a low risk of antiviral resistance following 48 weeks of adefovir; however, with extended treatment, the risk is significant, although not as great as lamivudine [38]. Among adults, there are more potent treatment options with increased antiviral effect than adefovir.…”
Section: Adefovirmentioning
confidence: 99%
See 1 more Smart Citation
“…3 summarizes the accumulation of resistance to approved nucleos(t)ide analogues after treating naı ¨ve patients for five consecutive years. [72][73][74][75][76] 2.4.3 Anti-HBV agents in clinical trials. None of the approved therapies (i.e.…”
Section: Hbvmentioning
confidence: 99%